Positive results for patients with COVID-19 discharged form hospital in Chongqing, China - Deng, Wang; Guang, Tian-wen; Yang, Mei; Li, Jian-rong; Jiang, De-peng; Li, Chang-yi; Wang, Dao-xin (BMC infectious diseases, 2020)
Since December 2019, over 80,000 patients with coronavirus disease 2019 (COVID-19) have been confirmed in China. With the increasing number of recovered patients, more attention should be paid to the follow-up of these patients. In the study, 576 patients with COVID-19 discharged from hospital in Chongqing, China from January 24, 2020, to March 10, 2020 were evaluated by viral nucleic acid tests for severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) to determine if they could be released from quarantine. Among the 576 patients, 61 patients (10.6%) had positive RT-PCR test results of SARS-CoV-2. We aimed to analyze the demographics, clinical characteristics and treatment of 61 patients. These positive patients were characterized by older age, chronic medical illness and mild conditions. 38 (62.3%) patients who were asymptomatic without abnormalities on chest radiographs were found in the positive with COVID-19. Also, they showed positive results of stool or sputum specimens with negative results of nasal and pharyngeal swab specimens. The median duration of positive result of SARS-CoV-2 was varied from 3 days to 35 days in the patients discharged from hospital with no family member infection. Multi-site screening of SARS-CoV-2 including nasal and pharyngeal swabs, stool and sputum specimens could be considered to improve the diagnosis, treatment and infection control in patients with COVID-19. Our findings provide the important information and clinical evidence for the improved management of patients recovered from COVID-19.